2007
DOI: 10.1097/mat.0b013e318050d607
|View full text |Cite
|
Sign up to set email alerts
|

Altered Proximal Aortic Stiffness and Endothelin Plasma Levels in Diabetic Patients With End-Stage Renal Disease

Abstract: Peripheral artery stiffness is altered in diabetic patients with end-stage renal disease (ESRD), whereas few data exist to confirm this trend for proximal aortic stiffness. The pulse wave velocity of the proximal aorta (PWVr) and of the carotid-to-femoral aortic segment (PWVcf) were determined by ultrasound imaging in 160 patients with ESRD (70 diabetic) and in 160 matched control subjects. Also, plasma levels of endothelin, homocysteine, and high-sensitivity C-reactive protein were determined in both groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Plasma ET‐1 is likely increased in dialysis patients for the same reasons as in CKD patients (inflammation, reduced clearance, hypertension and vascular injury) as well as due to erythropoiesis‐stimulating agents and flow through the arteriovenous fistula . In particular, there is a strong correlation between plasma ET‐1 and C‐reactive protein, atherosclerosis and proximal aorta stiffness in dialysis patients . Pre‐clinical studies indicate that ET‐1 may be important in vascular calcification in the setting of CKD , while ETA receptor blockade caused regression of vascular calcification in a model of isolated systolic hypertension .…”
Section: Endothelin Antagonists In End‐stage Kidney Diseasementioning
confidence: 99%
“…Plasma ET‐1 is likely increased in dialysis patients for the same reasons as in CKD patients (inflammation, reduced clearance, hypertension and vascular injury) as well as due to erythropoiesis‐stimulating agents and flow through the arteriovenous fistula . In particular, there is a strong correlation between plasma ET‐1 and C‐reactive protein, atherosclerosis and proximal aorta stiffness in dialysis patients . Pre‐clinical studies indicate that ET‐1 may be important in vascular calcification in the setting of CKD , while ETA receptor blockade caused regression of vascular calcification in a model of isolated systolic hypertension .…”
Section: Endothelin Antagonists In End‐stage Kidney Diseasementioning
confidence: 99%
“…Plasma ET-1 levels correlate with left ventricular hypertrophy (LVH) and arterial intima-media thickening in patients with end-stage renal disease (ESRD) [63]. There is also strong concordance between proximal aortic stiffness and ET-1 in diabetics with ESRD [64].…”
Section: Endothelin System and Blood Vesselsmentioning
confidence: 96%
“…In patients with end stage renal disease (ESRD), Demuth et al demonstrated that plasma ET-1 levels are elevated and associated with LVH and arterial intima-media thickening [152]. In diabetics with ESRD, proximal aortic stiffness and ET-1 levels are increased and the relationship between each is closely correlated [153]. Infusion of ET-1 into anesthetized sheep significantly increases PWV in the iliac artery and this effect can be reversed with administration of an ET A receptor antagonist [154].…”
Section: Endothelin Systemmentioning
confidence: 98%